The role of PAC adsorption-catalytic oxidation in the ultrafiltration performance for treating natural water: Efficiency improvement, fouling mitigation and mechanisms. (December 2021) - Cheng, Xiaoxiang; Hou, Chengsi; Li, Peijie; Luo, Congwei; Zhu, Xuewu; Wu, Daoji; Zhang, Xinyu; Liang, Heng
Abstract: Powdered activated carbon (PAC) has turned out to be an efficient adsorbent in drinking water treatment, whereas its application integrated with membrane filtration is still controversial because of the combined fouling effect between organic pollutants and PAC. To this end, an integrated process of combining PAC adsorption-catalytic oxidation and membrane filtration was proposed for natural surface water treatment. The synergistic effect of PAC and peroxymonosulfate (PMS) was confirmed through the generation of reactive oxidation species, and both radical oxidative pathways ( OH, SO4 − and O2 − ) and nonradical ( 1 O2 and PMS) pathways involved in the process. The removal efficiency of DOC and UV254 was significantly strengthened by PAC/PMS, with removal rates of 56.1% and 64.9%, respectively. The integration of PAC and PMS could significantly enhance the reduction of fluorescent organics, and pollutants with varying molecular weights. The fouling condition of membrane was dramatically alleviated, with the flux increased by 38.9%, and the reversible and irreversible resistances declined by 79.7% and 48.3%, respectively. The major fouling mechanism was significantly changed, and complete pore blocking always played a dominant role, rather than cake filtration. The effectiveness of PAC/PMS was further verified by the characterization of membrane surface morphologies and functional groups. Moreover, the attractive interactions between foulants and membrane were converted to repulsive interactions with the pretreatment of PAC/PMS. The proposed synergistic process was efficient and convenient, which could significantly improve the purification efficiency of conventional PAC-UF system in drinking water treatment. Graphical abstract: Image 1 Highlights: The process of PAC/PMS-UF was proposed for natural surface water treatment. PAC and PMS exhibited a synergistic effect by generating . OH, SO4 −, O2 − and 1 O2 . The removal efficiency of organic pollutants was significantly strengthened. Membrane fouling was alleviated with less foulants deposited on membrane surface. The attractions between foulants and membrane were converted to repulsions.